PERAN GAYA KEPEMIMPINAN TERHADAP BUDAYA ORGANISASI PADA HMPS FKIP ULM BANJARMASIN - Randy, Ahmad Abrar; Nur, Rahmat (Jurnal Tugas Akhir Mahasiswa Pendidikan Sosiologi, 2024)
Leadership in organizational culture is a determining factor for success in achieving the vision, mission, and goals of the organization. Appropriate and effective leadership serves as the foundation for organizational success. This research aims to describe the role of leadership style in organizational culture at HMPS FKIP ULM Banjarmasin. The objectives of this study are: 1) to describe the leadership style at HMPS FKIP ULM Banjarmasin, and 2) to describe the organizational culture at HMPS FKIP ULM Banjarmasin. Qualitative research is used. In addition, six informants who were selected through purposive sampling have been interviewed. The research collects data through observation, interviews, and documentation. Data is reduced, presented, and verified for analysis. The validity of the data is tested through triangulation of sources, techniques, and time. The research revealed that the leadership style of HMPS members, including character, communication, decision-making, motivation, and organizational environment, is democratic. Organizational culture, such as solidarity and cooperation, is also very important. Effective leadership involves providing support, nurturing relationships, and coordinating with stakeholders.